New Trends in the Development of the US-Japan Military and Political Relations - D. V. Streltsov (Vestnik MGIMO-Universiteta)
The article examines recent trends in the development of the US-Japan political and defense alliance, including the sphere of operational planning and coordination. A special attention is drawn to the problem of interaction between the two countries in the area of Ballistic Missile Defense, the problem of procurement American fighters F-35, as well as the issue of relocation of the Futemma base in Okinawa. The author reviews the results of the recent US-Japan Summit, held in Washington on April 30, 2012.